Copper(i)/succinic acid cooperatively catalyzed one-pot synthesis of organoselenium-propargylamines via A3-coupling. (22nd May 2018) - de Oliveira, Isadora M.; Pimenta, Daniel C.; Zukerman-Schpector, Julio; Stefani, Hélio A.; Manarin, Flávia
Abstract : Selenium propargylamines were synthesized via an A 3 -coupling approach using piperidine, p -methoxybenzaldehyde, and trimethylsilyl selenium–acetylene, catalyzed by copper(i ) chloride and succinic acid as an additive, in good to excellent yields. Abstract : Selenium propargylamines were synthesized via an A 3 -coupling approach using piperidine, p -methoxybenzaldehyde, and trimethylsilyl selenium–acetylene, catalyzed by copper(i ) chloride and succinic acid as an additive, in good to excellent yields. This method is advantageous in that desilylation of the trimethylsilyl selenium–acetylene occurs in situ . The reaction time was monitored by FTIR studies and a probable mechanism is described. Scale-up was also performed in satisfactory yield. These selenium propargylamines could be hydrohalogenated to synthesize halovinyl selenides. The stereochemistry was determined by treatment with n -butyllithium and the coupling constant ( J ) values in 1 H NMR spectra. The vinyl selenides were employed in Sonogashira cross-coupling reactions to produce the corresponding enynes, with yields ranging from moderate to good.